Autonomous Unmanned Underwater Vehicles Development Tendencies. (2015) - Gafurov, Salimzhan A.; Klochkov, Evgeniy V.
Abstract: This article gives a brief overview of the AUV development history from the beginning to the present day. We have considered different types of AUV from remote operated vehicles (ROV) to biomimetic AUV. Our goal is to define the vector of AUV development at an early date on the basis of the AUV history.